An Ecosystem Services Perspective for the Oceanic Eastern Tropical Pacific: Commercial Fisheries, Carbon Storage, Recreational Fishing, and Biodiversity - Martin, Summer L.; Ballance, Lisa T.; Groves, Theodore (Frontiers in Marine Science, 2016)
The ocean provides ecosystem services (ES) that support humanity. Traditional single-issue management largely failed to protect the full suite of ES. Ecosystem-based management (EBM) promotes resilient social-ecological systems that provide ES. To implement EBM, an ES approach is useful: 1) characterize major ES provided (magnitude, geographic extent, monetary value, trends, and stakeholders), 2) identify trade-offs, 3) determine desired outcomes, and 4) manage anthropogenic activities accordingly. Here we apply the ES approach (steps 1-2) to an open ocean ecosystem, the eastern tropical Pacific (ETP), an area of 21 million km2 that includes waters of 12 nations and the oceanic commons, using 35 years (1975-2010) of fisheries and economic data, and 20 years (1986-2006) of ship-based survey data. We examined commercial fisheries, carbon storage, biodiversity, and recreational fishing as the major provisioning, regulating, supporting, and cultural ES, respectively. Average catch value (using U.S. import prices for fish) for the 10 most commercially fished species was $2.7 billion yr-1. The value of carbon export to the deep ocean was $12.9 billion yr-1 (using average European carbon market prices). For two fisheries-depleted dolphin populations, the potential value of rebuilding carbon stores was $1.6 million (cumulative); for exploited fish stocks it was also $1.6 million (an estimated reduction of 544,000 mt). Sport fishing expenditures totaled $1.2 billion yr-1, from studies of three popular destinations. These initial, conservative estimates do not represent a complete summary of ETP ES values. We produced species richness maps for cetaceans, seabirds, and ichthyoplankton, and a sightings density map for marine turtles. Over 1/3 of cetacean, seabird, and marine turtle species occur in the ETP, and diversity (or density) hotspots are widespread. This study fills several gaps in the assessment of marine and coastal ES by focusing on an oceanic habitat, utilizing long-term datasets, mapping the spatial distribution of ecological components, and concentrating on an area beyond Europe and the USA. Our results improve our understanding of ETP ES, highlight their variety, and offer a new perspective for a fisheries-dominated system. This study sets the stage for further analyses of trade-offs, which can inform decisions about resource management and biodiversity conservation.